BEING AND PROBLEMS OF DEVELOPMENT OF GAS-TRANSPORT SYSTEM OF UKRAINE - Грудз, Володимир Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Description of the technical state of the gas-transport system of Ukraine is given, in particular transits gas pipelines, problems are examined on the way of its development.